Clustering of breakpoints on chromosome 10 in acute T-cell leukemias with the t(10;14) chromosome translocation. - Kagan, J (1989)
The T-cell receptor (TCR) alpha/delta chain locus on chromosome 14q11 is nonrandomly involved in translocations and inversions in human T-cell neoplasms. We have analyzed three acute T-lymphoblastic leukemia samples carrying a t(10;14)(q24;q11) chromosome translocation by means of somatic cell hybrids and molecular cloning. In all cases studied the translocation splits the TCR delta chain locus. Somatic cell hybrids containing the human 10q+ chromosome resulting from the translocation retain the human terminal deoxynucleotidyltransferase gene mapped at 10q23-q24 and the diversity and joining, D delta 2-J delta 1, regions of the TCR delta chain, but not the V alpha region (variable region of the TCR alpha chain), demonstrating that the split occurred within the V alpha-D delta 2 region. Molecular cloning of the breakpoint junctions revealed that the TCR delta chain sequences involved are made from the D delta 2 segment. The chromosome breakpoints are clustered within a region of approximately 263 base pairs of chromosome 10. The results suggest that the translocation of the TCR delta chain locus to a locus on 10q, which we have designated TCL3, results in deregulation of this putative oncogene, leading to acute T-cell leukemia.